Compassion-Based Therapy for Trauma-Related Shame and Posttraumatic Stress: Initial Evaluation Using a Multiple Baseline Design. Issue 2 (March 2017) - Au, Teresa M.; Sauer-Zavala, Shannon; King, Matthew W.; Petrocchi, Nicola; Barlow, David H.; Litz, Brett T.
Abstract: Accumulating research suggests that shame can strongly contribute to the development and maintenance of posttraumatic stress disorder (PTSD). Interventions that promote self-compassion have shown promise for reducing shame related to various clinical problems, but this approach has not been systematically evaluated for traumatized individuals. The aim of this study was to develop a brief compassion-based therapy and assess its efficacy for reducing trauma-related shame and PTSD symptoms. Using a multiple baseline experimental design, the intervention was evaluated in a community sample of trauma-exposed adults ( N = 10) with elevated trauma-related shame and PTSD symptoms. Participants completed weekly assessments during a 2-, 4-, or 6-week baseline phase and a 6-week treatment phase, and at 2 and 4 weeks after the intervention. By the end of treatment, 9 of 10 participants demonstrated reliable decreases in PTSD symptom severity, while 8 of 10 participants showed reliable reductions in shame. These improvements were maintained at 2- and 4-week follow-up. The intervention was also associated with improvements in self-compassion and self-blame. Participants reported high levels of satisfaction with the intervention. Results suggest that the intervention may be useful as either a stand-alone treatment or as a supplement to other treatments. Highlights: A compassion-based therapy was developed for trauma-related shame and PTSD. The intervention was evaluated in a multiple baseline experimental study. Treatment was associated with large, reliable reductions in PTSD symptoms and shame. Treatment gains were maintained at 4-week follow-up. Compassion-based therapy may be an effective treatment for shame-based PTSD.